PortMeteO radiosounding measurements during METEOR cruise M207 - Sebastian Wahl; Franz Kanngießer; Arne Leuzinger; Natalia Sudarchikova; Andebo Waza; Stephanie Fiedler (PANGAEA, 2025)
This dataset describes the non-standard meteorological data collected using the newly developed portable meteorological observatory (PortMeteO) during the METEOR Expedition M207 from Belem, Brazil (Jan 3rd, 2025) to Mindelo, Cabo Verde (Feb 11, 2025). Apart from validating the setup, the main purpose was to observe different properties of Saharan dust outbreaks. The ceilometer and disdrometer where operated 24/7 while the sun photometers where used at regular intervals during the day whenever clear sky conditions prevailed. Radiosondes where operated during between Jan 27 and Jan 30, 2025 to capture further details on the dust plume associated with a Saharan dust outbreak.